MODEL PEMBELAJARAN INTERAKTIF ISLAMI DI MI “SINAU” BERBASIS ANDROID - Wijayanti, Esti; Hidayati, Hanik; Meimaharani, Rizkysari (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Madrasah Ibtidaiyah (MI) is the most basic level of formal education in Indonesia and corresponds to primary schools administered by the Ministry of Religious Affairs. Madrasah Ibtidaiyah's education lasts for six years, from grades 1 to 6. Graduates of Madrasah Ibtidaiyah can continue their education at Madrasah Tsanawiyah or middle school. The purpose of this study is to create an interactive Islamic learning application consisting of several materials provided by researchers. There are also some quizzes to find students' benchmarks in collecting material using this model. Researchers used a research design based on the educational development methodology known as R&D (Research and Development). This study created the "SINAU" application, an interactive Islamic learning application consisting of several materials provided by the manufacturer. There are also some quizzes to find a student's benchmark in collecting material.